Effect of Body Mass Index on Abnormal Ovarian Secretion Hormones among Iraqi Women with Polycystic Ovarian Syndrome (PCOS) - Faraj, Rania M L; Jawad, Alaa H; Badr, Alaa H (Al-Nahrain Journal of Science, 2019)
Polycystic ovarian syndrome (PCOS) is the most common and complex endocrine disorder affecting women in the reproductive age. The etiology of this syndrome is not completely known, so there is a developing proof that supports genetic basis, PCOS has a strong familial preference. This study was carried out to investigate the effect of body mass index (BMI) on ovarian hormones in women with PCOS and healthy women. Eighty-three women aged (17-40) years were divided into two groups for testing (BMI less than 25 and more than 25). Hormonal study of Luteinizing hormone (LH), Androgen, Estradiol (E2) was done for each patient, the results of these hormones in patients compared with controls in both BMI groups with E2/T ratio showed a significant increase in patients women compared to controls in (p